(untitled) (Al-Academy, 2020)
The aim of the research is to identify the trends of Saudi society towards visiting art galleries and museums in light of economic and social transformations after the implementation of the 2030 vision plans. The importance of the research is to track the reasons behind the reluctance of members of society to visit such cultural institutions, and to plan proposals and recommendations for how to attract members of society and motivate them. This research followed the descriptive approach, and the study sample reached 103 members of the Saudi community. several research tools were used in this research such as questionnaire, personal interviews in addition to the researcher notes. The results concluded that the art galleries attract the apostates from members of the Saudi society for their desire to enrich their artistic culture. Further, it was showed that the National Museum in Riyadh, was the most museum visited by members of the research sample, but there are a number of obstacles that affects the low percentage or the frequency of the visits. The research concludes with a number of recommendations to raise and enrich the visit percentages